Modelagem hidrodinâmica no Baixo São Francisco e análise da quantidade e da qualidade da água para irrigação - Chagas, Rogério Moreira (2009)
The aims of the present work were to simulate critical events of outflows in order to study the hydrodynamic behavior in the lower at the San Francisco river, by using hydrodynamic model HEC-RAS, and to analyze the water availability in the Perimeter Irrigated of Propria (state of Sergipe, Brazil) in the aspects of amount and quality of water being used the network flow model AcquaNet. In the State of Sergipe the dependence of the waters of the San Francisco river is increasing. Cities, factories and perimeter irrigation supplyment are the mainly attendant demands with the directly capitation in San Francisco river or in some of its tributaries. The construction of barrages for energy generation and attenuation for floods, the withdrawal of the riparian vegetation and the pollution of waters of the San Francisco river and its tributaries, are characterized as the most serious problems that can compromise the water availability in amount and quality in the region at the Lower San Francisco in the medium and long term. The main impacts generated in result of the alterations in the natural regimen of outflows are: the sedimentation of the main channel, the interruption of the natural cycle of full in the lateral lakes, the loss of cultivated areas, the disruption of containment levees and the endangerment of the processes of extraction and draining of the irrigation perimeters. To guarantee the water supplyment in amount and quality for agroecosystems and ecosystems associates to the river depends on the planning and management of the water resources that must be thought adopting the hydrographic basins as basic units of planning.